a* values to follow lycopene concentration during ripening and storage of tomato (cv. Caruso) - Schauwers, Axelle (2006)
The ripening of tomato fruit is a highly regulated process during which colour, flavour, aroma and texture change in a coordinated manner. This research work aims to correlate the colour changes measured objectively with the lycopene concentration in tomatoes during ripening at room temperature (21 and 26°C). These results were compared with colour and lycopene content of pink and light red tomatoes stored at 14°C, temperature used to prevent ripening and therefore extend the shelf life of the fruits. The duration of heat treatment at 100ºC was previously optimized in order to release the maximum lycopene from chromoplasts during extraction. An a* value of 20 for the peel corresponds to an increase of lycopene content of Caruso tomato from 9 to 43 mg/100 g TSS, at room temperature. The shelf life of pink and light red tomatoes can be extended to two weeks at 14ºC without loss of lycopene content, presenting the same content as green tomatoes ripened at room temperature for one week.